189k views
0 votes
I am really confused on how to do this. ​

I am really confused on how to do this. ​-example-1
User Weiweishuo
by
4.9k points

1 Answer

6 votes

Explanation:

Ok, so in a standard equation, there can’t be any fractions, so you would have to multiply everything by 3, making the equation 3y+3=2(x-8) (p.s. don’t multiply the parentheses, leave the numbers in them alone for now). Then, you would go through with the equation process: 3y+3=2x-16. You move the 3 over to the right to make 3y=2x-19. Move the x to the left, -2x+3y=-19. But, there is a problem. The first term of this equation can’t be negative(yes, in standard form, x has to come first). So, you have to multiply everything by -1, resulting in the answer 2x-3y=19. I hope this helps!(The format for a standard form equation is: Ax+By=C).

User Sam Salisbury
by
6.3k points